Production and Nutrition of Khi Lek (Siamese cassia) Curry from Central Thailand - Chowladda Teangpook; Urai Paosangtong; Yenjai Titatarn; Somchit Onhem; Winus Puminat (Agriculture and Natural Resources, 2011)
Khi Lek (locally called Siamese cassia) curry is an ancient food throughout Thailand that uses the tips, young leaves and young flowers of the plant. However, as they have a bitter taste, the Thai people must boil them in water 2–3 times before use. Boiling may impact on the characteristics of Khi Lek young leaves (KL). Thus, this project studied the effect of sodium chloride and eggplant, the optimum time (minutes) and number of times boiled of KL for curry making and its nutrition. The results showed that the anhydrobarakol content in KL boiled in water alone, in KL boiled in water containing sodium chloride and in KL boiled in water containing eggplant were not significantly different (P > 0.05). The anhydrobarakol content in boiled KL decreased with increasing time of boiling and/or the number times boiled. KL for curry should be boiled twice in a volume of water six times the KL weight, for 3 min/time. KL curry had a very low anhydrobarakol content (0.17 mg by fresh weight) and a low tendency to cause liver toxicity.